1999
DOI: 10.1095/biolreprod60.2.349
|View full text |Cite
|
Sign up to set email alerts
|

Superovulatory Response of One Ovary Is Related to the Micro- and Macroscopic Population of Follicles in the Contralateral Ovary of the Cow

Abstract: We hypothesized that the ovulatory response of one ovary to FSH would be related positively to the size of the primordial and growing pools of follicles in the other ovary. Nonlactating cows (n = 26) were unilaterally ovariectomized and 2 days later were superovulated. The superovulatory response was classified as Low (< 5 corpora lutea [CL]), Medium (5-14 CL), or High (> 14 CL). Surface follicles on the ovary removed before superovulation were classified as small (1-3 mm), medium (3-7 mm), or large ( > 7 mm),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
2
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 23 publications
11
55
2
5
Order By: Relevance
“…Such responsiveness is negatively associated with aging and is linked to a reduction in number of follicles and oocytes in ovaries in women (Beckers et al 2002, Styer & Toth 2011, Dewailly et al 2014 and in cattle (Kawamata 1994, Cushman et al 1999, Taneja et al 2000, Singh et al 2004. We documented for the first time that young adult cattle with low AFC have a diminished responsiveness to superovulation (lower number of corpora lutea and of recovered embryos/unfertilized oocytes) and produced fewer high-quality embryos compared to age-matched cattle with high AFC (Ireland et al 2007).…”
Section: Superovulationmentioning
confidence: 65%
See 1 more Smart Citation
“…Such responsiveness is negatively associated with aging and is linked to a reduction in number of follicles and oocytes in ovaries in women (Beckers et al 2002, Styer & Toth 2011, Dewailly et al 2014 and in cattle (Kawamata 1994, Cushman et al 1999, Taneja et al 2000, Singh et al 2004. We documented for the first time that young adult cattle with low AFC have a diminished responsiveness to superovulation (lower number of corpora lutea and of recovered embryos/unfertilized oocytes) and produced fewer high-quality embryos compared to age-matched cattle with high AFC (Ireland et al 2007).…”
Section: Superovulationmentioning
confidence: 65%
“…This could explain why granulosa cells in cattle with a low AFC were refractory to FSH action and consequently produced less AMH compared to granulosa cells from cattle with a high AFC. In addition, the refractoriness of granulosa cells to FSH could also at least partially explain why cattle (Kawamata 1994, Cushman et al 1999, Taneja et al 2000, Singh et al 2004, Ireland et al 2007) and women (Beckers et al 2002, Broekmans et al 2006, Styer & Toth 2011, Dewailly et al 2014) with a small ovarian reserve and correspondingly chronically high FSH secretion during reproductive cycles respond poorly to FSH stimulation during assisted reproductive technologies.…”
Section: Granulosa Cellsmentioning
confidence: 99%
“…The application of all time periods to each individual animal was designed to minimize individual variations in the genomic response. This design is even more important in the context of known variability in the response to hormones both across and within individuals (Kawamata 1994, Cushman et al 1999, Rico et al 2009). The physiological observations of oocyte quality as reflected by the blastocyst rates across coasting duration indicates an initial increase (20-68 h) followed The granulosa cell expression during this period of increasing competence is associated with expression of genes leading to apoptosis increases (FOXO3, STAT6, and CASP8) and cellular proliferation decreases (TP53, SMARCB1, STAT4, and CCL2).…”
Section: Discussionmentioning
confidence: 99%
“…The number of small follicles 3-6 mm in diameter on both ovaries before the superovulatory treatment was found to be significantly correlated with the numbers of corpora lutea after superovulation (r = 0.440, P < 0.001), total recovered ova (r = 0.503, P < 0.001) and transferable recovered embryos (r = 0.482, P < 0.001). More recently, Cushmann et al [12] found that the number of CL is correlated positively with the total number of primordial, tertiary, and medium surface follicles. The number of CL is related to the number of tertiary follicles in a positive linear manner and the number of medium follicles in a positive quadratic manner.…”
Section: Conclusion For Practisementioning
confidence: 98%